School Inspection Framework Change Factors and their Impact on Inspection Protocols, Practices, and Inspector Competencies in UAE - EL SAADI, DINA HUSSEIN (2025)
Limited insight exists on educational policy and operational adaptations of inspector competencies, school protocols and practices in the face of changing school inspection frameworks. This gap emanates from the complex, dynamic, and non-constant nature of school inspection framework change factors. These factors and their salience at any given moment of introducing a new school inspection framework evolve, eluding common or pre-defined conceptual direction. This study utilised systems dynamics theory, complex adaptive theory, communicative action theory, and competency theory of school inspectors, employing a sequential exploratory mixed method to explore the factors of change in the “UAE School Inspection Framework” and closely evaluate the degree to which the change factors affect the protocols and practices as well as the required competencies of inspectors to operationalise the framework. Data were collected from inspectors, educational leaders, and experts in educational systems in the UAE context. The results show that the socio-economic, knowledge economy & education, educational system AI & technology, and inspection visits & outcomes are the main factors that account for the evolution and changes of the UAE framework. Survey evidence establishes that these factors positively influence the inspection protocols & practices. Furthermore, the protocols and practices have an essential and positive role to play in the required inspectors’ competencies. Based on the study’s results, future research to validate these factors and in-depth studies over extended periods are suggested to better understand the dynamic characteristics of school inspection change factors and their impact on schools’ protocols, practices, and inspectors’ competencies. The UAE government and educational entities are advised to adopt a dynamic system perspective to plan and implement changes in the school framework, aligning it with evaluators' competencies to improve future evaluation outcomes, recommendations, and policies.